Sinterability and mechanical properties of MnO2-doped Y-TZP: the effects of holding time variations - Amiriyan, M.; Satgunam, M.; Sivakumar, S.; Singh, R.; Tolouei, R. (2nd International Conference on Mechnaical and Aerospace Engineering (ICMAE 2011), 2012)
the effect of holding time variation and sintering temperature on the mechanical properties and sinterability of yttria stabilized tetragonal zirconia doped with 1 wt. MnO2 was investigated. Samples were sintered at 1150-1500 degrees C with holding times varying from 12 and 120 minutes. Comparing to the MnO2-doped Y-TZP, longer holding time resulted in enhanced densification of the undoped Y-TZP samples. In the case of MnO2-doped Y-TZP however, Bulk density, Young's modulus, Vickers hardness and fracture toughness results show the beneficial effect of MnO2 in enhancing the densification of Y-TZP ceramics.